Bone Metabolism During Strict Head-Down Tilt Bed Rest and CO2 Exposure. (14th June 2022) - McGrath, Emily; Frings-Meuthen, Petra; Sibonga, Jean; Heer, Martina; Clement, Gilles; Mulder, Edwin; Zwart, Sara; Smith, Scott
Abstract: Objectives: Carbon dioxide (CO2 ) levels on board the International Space Station reach 10× those of outdoor terrestrial levels. We report here studies assessing whether increased levels of ambient CO2 contribute to elevated bone resorption characteristically observed with bed rest as an analog for skeletal unloading during spaceflight. Methods: Data are reported from two ground-based studies which included 12 male and 7 female subjects placed in a strict −6° head-down tilt (HDT) position for 30 days at 0.5% ambient CO2 or 60 days with nominal environment (0.04% CO2 ). Subjects were neither afforded a pillow nor allowed to use an elbow while eating to increase headward fluid pressure. Bone mineral density (BMD) and bone mineral content (BMC) were measured with dual-energy X-ray absorptiometry. Blood and urine were collected before and during HDT for analysis. Results: There was no change in BMD or BMC. Excretion of collagen crosslinks increased during HDT (p < 0.001) with no additive effect of CO2 . Serum and urine mineral concentrations were not affected by CO2 . Serum PTH and 1, 25-deoxyhydroxyvitamin D were both reduced during bed rest (p < 0.0001), likely secondary to calcium efflux from bone, but with no additive effect of CO2 exposure. These changes reinforce the impact of decreased mechanical loading on bone and mineral homeostasis and the efficacy of the strict HDT model. Conclusions: Exposure to 0.5% CO2 for 30 days did not exacerbate bone resorption during strict HDT bed rest. Future research on bone metabolism at varied CO2 levels is needed to clarify a risk ceiling for bone resorption, especially as missions progress beyond low-Earth orbit. Funding Sources: The data reported here were from the NASA Human Research Program Standard Measures Cross-Cutting Project. Funding was provided by the NASA Human Research Program's Human Health Countermeasures Element. ERM was funded through a NASA Summer Science Institute Fellowship.